Developing Cue Card Media To Teach Speaking Skill For Ninth Grade Students At SMP Hasanuddin - Sabila, Naumi Asfarina; Mubarok, Tyas Alhim; Widi, Widiarini; Makrifah, Istina Atul (Jurnal Pembelajaran dan Ilmu Pendidikan, 2025)
This study aims to create cue card media as an instructional aid to enhance the speaking skills of ninth-grade students at SMP Hasanuddin. The research adopts the Research and Development (R&D) approach, specifically utilizing the 4-D model, which includes the stages of Define, Design, Develop, and Disseminate. The background of this study stems from students' difficulties in speaking English, particularly in expressing ideas fluently and engaging in meaningful conversations. To address this issue, the researcher designed cue cards containing prompts and vocabulary that support guided dialogues between students.The developed product underwent validation by a media expert and a material expert, and was subsequently tested through student trials. The material validation score was 93%, the media validation score was 95%, and the student satisfaction score was 87%, all of which indicate that the media is highly feasible. The media enables students to engage in paired conversations using situational prompts provided through cue cards. Based on the findings, this learning tool is deemed both effective and practical in enhancing students’ speaking abilities and may serve as an alternative instructional resource in English language teaching